GIS-based analysis of water quality risk factors and CKDu prevalence in Northern Yobe State, Nigeria - Babagana-Kyari, Modibbo; Yaro, Nura Ahaji; Yakasai, Kabiru M. (Indonesian Journal of Applied Environmental Studies, 2024)
Chronic Kidney Disease (CKDu) presents a major public health challenge in Northern Yobe State, Nigeria, particularly in the Bade community, where water quality is overly suspected to influence its prevalence. This study employs a Geographic Information Systems (GIS)-based framework to analyze the spatial distribution of CKD in relation to water quality parameters. Advanced spatial analysis techniques, including hexagonal tessellation and Moran's I for spatial autocorrelation, were utilized alongside community-based surveys conducted using Kobotoolbox and Qfield applications to map CKD hotspots. The Moran's I Index of 0.1046, with a z-score of 4.9546 and a p-value of 0.000001, indicates significant clustering of CKD cases rather than random distribution across the study area. Water samples from 30 water facilities, with 10 from each classified hotspot, were analyzed for nephrotoxic heavy metals, ionic concentrations, and hardness using an Atomic Absorption Spectrometer (Model 210V-GP). The spatial distribution of these parameters was modeled using Inverse Distance Weighting (IDW) interpolation in ArcGIS Pro 3.4. Descriptive statistics, hazard index calculations, and Water Quality Index (WQI) assessments were conducted, with box plots facilitating comparative analysis across High, Medium, and Low disease areas. ANOVA and Tukey's HSD post-hoc tests were performed to compare specific water parameters between the disease hotspots and water facilities. The results revealed elevated concentrations of nephrotoxic heavy metals in high-disease hotspots, with maximum values observed for Arsenic (0.21 mg/L), Cadmium (0.30 mg/L), Lead (0.23 mg/L), Chromium (0.50 mg/L), and Fluoride (55 mg/L). Additionally, Nitrite and Nitrate levels exhibited high Hazard Quotients, all surpassing WHO guidelines for safe drinking water. These findings underscore the potential health risks posed by these contaminants in affected areas. Results demonstrate a significant link between the prolonged use of handpumps water and high prevalence of chronic kidney disease incidence (CKD) among affected households. Additionally, the study identified strong spatial correlations between CKD incidence and high concentrations of nephrotoxic heavy metals in water from handpumps, providing critical insights for targeted public health interventions and guiding future research efforts.